ANALISIS PERBEDAAN RETURN SAHAM SEBELUM DAN SESUDAH MELAKUKAN STOCK SPLIT PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Winda Rika Lestari (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2012)
Stock split is one of corporate action which done by company with the purpose to arrangethe stock price which traded become more active. The purpose of this research is to analyze thedifferences of stock return and stock liquidity before and after stock split at companies listed inIndonesia Stock Exchange Periode 2005-2009. The stock liquidity in this research measured usingthe trading volume parameter because the trading volume is the increasing of buying and sellingactivity by the investor in Indonesia Stock Exchange. The characteristic of this research is eventstudy, that is the study to learn the market reaction toward an event or the information of eventpublished as an announcement. The samples in this research are 27 companies with purposivesampling technique, that is using stock split sample in year 2005-2009 and does not perform theother corporate action. The analysis model is used paired sample t-test by comparing 15 days beforeand 15 days after stock split. The result of this research shows that there is no the average ofsignificant differences among stock return and after stock split, while the stock liquidity shows thatthere is the average of significant differences volume before and after stock split.